Study of environmental impact of the artisan auriferous extraction within the political jurisdiction of the district of Santa Rosa de Quives, year 2006 - Gallarday Bocanegra, Tomás (2006)
This report presents the results of the Study of Environmental Impact that has been elaborated within the frame of support to the community by the UNMSM, the one that is authorized to make environmental impact works, consequently its educational ones make works of environment like the made one in the physical surroundings of the informal or artisan miners who come operating native gold and gold within sulfides, in an area of 320 000 has, located in the line of summits located within the hydrographic basins Chillón and Seco river, located in Batán’s hills, Huaycoloro, Loma Grande, Marota, Pan de Azúcar, Reloj and Pampa river, activity which has originated negative and positive impacts, reason for the present work, that in its integral part the protection of environment considers, the health, the well-being of the artisan, settler mining workers of the Santa Rosa de Quives’s communitarian district of community of Jiquicamarca; tolerable profit in the sustainable improvement in the conditions of life also looks for with the study the settlersg, as it is the harmonious or amical coexistence among them (miners, settlers, cattle dealers and agriculturists)